Puntos de quiebre después de la Conferencia de Durban (2001) - Espinosa, Eduardo Luis (SocietàMutamentoPolitica, 2018)
In 2001, it was held the “World Conference against Racism, Racial Discrimination, Xenophobia, and Related Intolerance” in Durban, South Africa. This essay revises the points where the Latin American denial of racism was broken, for the academy to go along with a civil action, to examine and to criticize discrimination and prejudice for somatic motives. We analyze the four break points, from that date, whereby the recognize of the existence of racism has been inescapable: (1) the violence, that affect by far indigenous people and Afro-descendants; (2) the violation of rights of those ethnic groups; (3) their invisibility; (4) their crossroad in the midst of the inequality on Latin America.